A hypertension-associated mitochondrial DNA mutation introduces an m1G37 modification into tRNAMet, altering its structure and function - Mi Zhou; Ling Xue; Yaru Chen; Haiying Li; Qiufen He; Bibin Wang; Feilong Meng; Meng Wang; Min‐Xin Guan (2017)
Defective nucleotide modifications of mitochondrial tRNAs have been associated with several human diseases, but their pathophysiology remains poorly understood. In this report, we investigated the pathogenic molecular mechanism underlying a hypertension-associated 4435A→G mutation in mitochondrial tRNAMet. The m.4435A→G mutation affected a highly conserved adenosine at position 37, 3′ adjacent to the tRNA's anticodon, which is important for the fidelity of codon recognition and stabilization. We hypothesized that the m.4435A→G mutation introduced an m1G37 modification of tRNAMet, altering its structure and function. Primer extension and methylation activity assays indeed confirmed that the m.4435A→G mutation created a tRNA methyltransferase 5 (TRMT5)–catalyzed m1G37 modification of tRNAMet. We found that this mutation altered the tRNAMet structure, indicated by an increased melting temperature and electrophoretic mobility of the mutated tRNA compared with the wildtype molecule. We demonstrated that cybrid cell lines carrying the m.4435A→G mutation exhibited significantly decreased efficiency in aminoacylation and steady-state levels of tRNAMet, as compared with those of control cybrids. The aberrant tRNAMet metabolism resulted in variable decreases in mitochondrial DNA (mtDNA)-encoded polypeptides in the mutant cybrids. Furthermore, we found that the m.4435A→G mutation caused respiratory deficiency, markedly diminished mitochondrial ATP levels and membrane potential, and increased the production of reactive oxygen species in mutant cybrids. These results demonstrated that an aberrant m1G37 modification of mitochondrial tRNAMet affected the structure and function of its tRNA and consequently altered mitochondrial function. Our findings provide critical insights into the pathophysiology of maternally inherited hypertension, which is manifested by the deficient tRNA nucleotide modification. Defective nucleotide modifications of mitochondrial tRNAs have been associated with several human diseases, but their pathophysiology remains poorly understood. In this report, we investigated the pathogenic molecular mechanism underlying a hypertension-associated 4435A→G mutation in mitochondrial tRNAMet. The m.4435A→G mutation affected a highly conserved adenosine at position 37, 3′ adjacent to the tRNA's anticodon, which is important for the fidelity of codon recognition and stabilization. We hypothesized that the m.4435A→G mutation introduced an m1G37 modification of tRNAMet, altering its structure and function. Primer extension and methylation activity assays indeed confirmed that the m.4435A→G mutation created a tRNA methyltransferase 5 (TRMT5)–catalyzed m1G37 modification of tRNAMet. We found that this mutation altered the tRNAMet structure, indicated by an increased melting temperature and electrophoretic mobility of the mutated tRNA compared with the wildtype molecule. We demonstrated that cybrid cell lines carrying the m.4435A→G mutation exhibited significantly decreased efficiency in aminoacylation and steady-state levels of tRNAMet, as compared with those of control cybrids. The aberrant tRNAMet metabolism resulted in variable decreases in mitochondrial DNA (mtDNA)-encoded polypeptides in the mutant cybrids. Furthermore, we found that the m.4435A→G mutation caused respiratory deficiency, markedly diminished mitochondrial ATP levels and membrane potential, and increased the production of reactive oxygen species in mutant cybrids. These results demonstrated that an aberrant m1G37 modification of mitochondrial tRNAMet affected the structure and function of its tRNA and consequently altered mitochondrial function. Our findings provide critical insights into the pathophysiology of maternally inherited hypertension, which is manifested by the deficient tRNA nucleotide modification.